Are children with clinical obesity at increased risk of inpatient hospital admissions? An analysis using linked electronic health records in the UK millennium cohort study. Issue 6 (18th January 2019) - Griffiths, Lucy J.; Cortina‐Borja, Mario; Bandyopadhyay, Amrita; Tingay, Karen; De Stavola, Bianca L.; Bedford, Helen; Akbari, Ashley; Firman, Nicola; Lyons, Ronan A.; Dezateux, Carol
Summary: Background: Few studies have examined health service utilization of children with overweight or obesity by using linked electronic health records (EHRs). Objective/Methods: We analysed EHRs from 3269 children (1678 boys; 51.3% [weighted]) participating in the Millennium Cohort Study, living in Wales or Scotland at age seven whose parents consented to record linkage. We used height and weight measurements at age five to categorize children as obese (>98th centile) or overweight (>91st centile) (UK1990 clinical reference standards) and linked to hospital admissions, up to age 14 years, in the Patient Episode Database for Wales and Scottish Morbidity Records. Negative binomial regression models compared rates of inpatient admissions by weight status at age five. Results: At age five, 11.5% and 6.7% of children were overweight or obese, respectively; 1221 (38%) children were subsequently admitted to hospital at least once. Admissions were not increased among children with overweight or obesity (adjusted rate ratio [RR], 95% confidence interval [CI]: 0.87, 0.68‐1.10 and 1.16, 0.87‐1.54, respectively). Conclusions: In this nationally representative cohort of children in Wales and Scotland, those with overweight or obesity at entry to primary school did not have increased rates of hospital admissions in later childhood and early adolescence.